2020
DOI: 10.1021/acssuschemeng.0c04583
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Flexible Poly(dimethylsiloxane) Composite Sensors Based on Flame-Synthesized Carbon Foam Made of Vertical Carbon Nanosheet Arrays

Abstract: A simple approach for the flame synthesis of carbon foam (FCF) via one-step catalytic deposition of carbon on a Ni template was developed. FCF was deposited within 5 min at ∼500 °C in an alcohol flame and the foam strut wall was found to be actually made of vertical carbon nanosheets. The carbon strut layer displayed a distinctive morphology between its two surface sides. The rough inner surface of the carbon strut originated from the vertically aligned carbon sheets, while some short carbon nanotubes with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Such a rich porous structure results from the metal framework template, which acts as the catalytic substrate for continuously growing graphene. Similar to the 3D porous amorphous carbon fabricated with the flame coating of Ni foam [27], grain boundaries replicating Ni substrate could be clearly observed in the high-magnification SEM image of the 3DG strut surface (see the inset in Figure 1b). Evidently, the graphene surface of 3DG is totally different from the conventional 2D graphene products, whose smooth surface is clearly shown as Figure 1a.…”
Section: Structure Characterization Of G and 3dgmentioning
confidence: 63%
“…Such a rich porous structure results from the metal framework template, which acts as the catalytic substrate for continuously growing graphene. Similar to the 3D porous amorphous carbon fabricated with the flame coating of Ni foam [27], grain boundaries replicating Ni substrate could be clearly observed in the high-magnification SEM image of the 3DG strut surface (see the inset in Figure 1b). Evidently, the graphene surface of 3DG is totally different from the conventional 2D graphene products, whose smooth surface is clearly shown as Figure 1a.…”
Section: Structure Characterization Of G and 3dgmentioning
confidence: 63%
“…A similar interpretation is supported by Kim et al, who observed that the sensitivity of a piezoresistive pressure sensor is proportional to the nanostructure density. [46][47][48] In addition, the nanorods of the shAAO-replicated PUA exhibited a smaller diameter of 292.2 AE 26.4 nm, resulting in a low surface coverage of 34.6%. Therefore, the contact area between the upper and lower PUA nanorods can be changed sensitively because of their easy engagement with the pressure applied to the sensing medium, which improves the sensitivity and linearity of the sensing signals in the shAAO-pressure sensor.…”
Section: Materials Advancesmentioning
confidence: 99%
“…Due to its time-saving, energy-conserving, and eco-friendly characteristics, and its convenience of operation, the flame synthesis of carbon materials has drawn growing attention. Carbonaceous nanomaterials in various forms, including 3D foam, 2D layer and 1D nanotube/nanofiber, have been deposited by this method on various substrates recently, including metals [ 24 , 25 , 26 ], inorganic oxides [ 27 ] and carbon fibers [ 28 ]. However, little information on the surface protection performance of the flame-deposited carbon (FDC) layers in comparison with its graphene counterpart is available at present, as well as on their anti-corrosion mechanisms.…”
Section: Introductionmentioning
confidence: 99%